WAYANG PANCASILA AS A POLITICAL EDUCATION EFFORTS IN THE GLOBAL ERA - Sugiaryo; Trisiana, Anita (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of writing this article, is to analyze and conduct an assessment of the right political education that can be done to influence the generation of milines in understanding the ideology of the nation and its local culture. The method used is analyzed using conceptual and procedural studies that lead to conclusions. Furthermore this research methodology uses Grounded Theory Methodology which can be used to develop theories through qualitative research conducted systematically and fundamentally. The results of the analysis show that in the era of wayang reforms it became a medium for campaigning, legitimizing, and conveying the messages of certain political parties . So shadow puppets can be used as one of the media of political education.Pancasila has been proven for years to be able to unite a very pluralistic Indonesia. The challenge now is precisely how to embody the values of Pancasila, so that it can be understood by the community and practiced in daily life. The Compilation of Culture and Politics in the form of "Wayang Pancasila" is one of the latest models to realize political education for millennials in the current global era.